Comparison of Fecal Methanogenic Archaeal Community Between Erhualian and Landrace Pigs Using Denaturing Gradient Gel Electrophoresis and Real-Time PCR Analysis - Yong SU; Hauke Smidt; Wei-Yun ZHU (Journal of Integrative Agriculture, 2014)
Erhualian and Landrace breeds are typical genetically obese and lean pigs, respectively. To compare the fecal methanogenic Archaeal community between these two pig breeds, fecal samples from different growth phase pigs were collected and used for PCR-denaturing gradient gel electrophoresis (DGGE) with two primer pairs (344fGC/519r and 519f/915rGC) and real-time PCR analysis. Results showed that a better separation and higher quality of bands pattern were obtained in DGGE profiles using primers 344fGC/519r as compared with primers 519f/915rGC. Sequencing of DGGE bands showed that the predominant methanogens in the feces of Erhualian and Landrace pigs belonged to Methanobrevibacter spp. and Methanosphaera spp. Real-time PCR analysis revealed that there was no significant difference in the numbers of fecal total methanogens between Erhualian and Landrace pigs; however, pig growth phase affected the numbers of 16S rRNA genes of total methanogens and Methanobrevibacter smithii. Dissociation curves of methyl coenzyme-M reductase subunit A (mcrA) gene fragments amplified with real-time PCR showed all samples possessed a single peak at 82°C, which might be associated with M. smithii. Samples from the same growth phase of each breed showed good replicative dissociation curves. The results suggest that the growth phase (including diet factor) other than genotype of pig may affect the fecal methanogenic Archaeal community of pigs.